If it's not what You are looking for type in the equation solver your own equation and let us solve it.
-11=k3+-9
We move all terms to the left:
-11-(k3+-9)=0
We add all the numbers together, and all the variables
-(+k^3+-9)-11=0
We use the square of the difference formula
-(+k^3-9)-11=0
We get rid of parentheses
-k^3+9-11=0
We do not support ekpression: k^3
| 1-5n-3=-7 | | -1.5(w+4)=4w-5 | | 2a-20=6a | | k+–1=–10 | | 5a-2=-9a+8 | | 15x+5=775 | | 37+5n=8(-3-7n) | | -7x+8=2x+6 | | 3(x-4)-7=-(-7x+5)-2 | | x/5+13=22 | | 5y+3y+2=18 | | 8n-5n=1 | | -12=-4p | | 3)5a-2=-9a+8 | | 48=5n+8 | | 6y-4y-15=13.44 | | 6b+1-5=8 | | -4-6b=-76 | | 5x+6x-20+3x-46=180 | | (3x-6)+130+(8x+4)=180 | | -16+7=35-x | | 6=-2(a-2) | | 99x–15=45 | | 32h+24=3h-11 | | 4/3=(x+10)/(15) | | 3k+8(2k-6)=2+14k | | 3x=8=13 | | 11+x/2=19 | | 30x-10=300 | | –10+7f=5f | | 9x+18=50 | | 20–5f=15f |